Study on Prescribing Pattern of Antibiotics in a Pediatric Out-Patient Department in a Tertiary Care Teaching and Non-Teaching Hospital - Malpani, Ashok Kumar; Waggi, Manjunath; Rajbhandari, Asmila; Kumar, Gunda Anil; Nikitha, Reddy; Chakravarthy, Alapathy Kalyan (Indian Journal of Pharmacy Practice)
Aim: The aim of the study is to conduct a prospective study on prescribing pattern of antibiotics in the out-patient department of Pediatrics and to evaluate the rational use of antibiotics. Methods: The study was conducted with a sample size of 480 patients for a period of 6 months at a Tertiary Care Teaching and Non-teaching Hospital after taking consent from both the hospitals. Results: In our study, a total of 480 prescriptions, hospital 1:225/129 and hospital 2: 225/154 were screened. Out of which 129(57.3%) and 154(60.39%) contained antibiotics and the average number of drugs was 2.93 ± 0.96 and 2.94 ± 0.9 for hospital 1 and 2 respectively. Majority of the prescriptions contained only one antibiotic. Moderate drug interactions of 85% and minor interactions of 15% were found from both the hospitals. Most common diseases found were upper respiratory tract infections (URTI-25.58%), fever (25.58%), gastroenteritis (GE) 17.82%) in hospital 1 and fever (22.72%), URTI (20.12%), LRTI (14.93%), GE (19.48) and UTI (16.23%) in hospital-2.Commonly prescribed antibiotic class and drugs was penicillin‑amoxicillin(18.18%)-hospital1,cephalosporins-cefixime(32.14%), ceftriaxone (21.42%) and cefodoxamine (40.17%)-hospital 2. The commonly used antibiotic combination was amoxicillin + clavulanic acid (hospital1:75%, hospital2-100%). The average total prescription cost and antibiotic cost was Rs. 96.96 and Rs. 45.30 (hospital 1), and Rs. 69.80&Rs. 39.60. (hospital 2) respectively. Conclusion: The total number of drugs and the number of antibiotics prescribed were found to be rational in both the hospitals. However more rationality was observed in non-teaching hospital with regard to prescribing pattern as well as economic criteria compared to teaching hospital.
Keywords: Prescribing pattern; Antibiotic; Outpatient; Paediatric